Blood glucose management for a patient with esophageal foreign body-induced esophageal perforation combined with mediastinal infection (1例食管异物穿孔伴纵隔感染患者的血糖管理) - LI Pengping (李鹏萍); SUN Yulian (孙玉莲) (Association of Integrative Nursing, 2021)
An emergency drainage of the mediastinal abscess using incision is necessary in the treatment of esophageal foreign body-induced esophageal perforation combined with mediastinal infection. It is also required to enhance the infection control and postoperative nutrition support for the patient. This paper summarized the treatment and nursing management of a patient with esophageal foreign body-induced esophageal perforation combined with mediastinal infection. Comprehensive nursing interventions including airway management, catheter management, enteral nutrition support, skin care, observation on postoperative complications were carried out. The Plan-Do-Check-Action cycle was adopted in the blood glucose management. The patient had good glycemic control and did not develop hypoglycemia during hospitalization. (食管异物发生食管穿孔及严重的纵隔感染表现时, 应尽早行纵隔脓肿切开引流, 同时积极控制感染, 术后做好营养支持。本文报道一例1例食管异物穿孔伴纵隔感染患者的治疗及护理措施, 术后实施气道护理、导管管理、肠内营养护理、皮肤护理、并发症观察及护理等综合护理措施, 采用PDCA循环加强患者血糖管理。患者住院期间血糖控制良好, 未发生低血糖。)